Apennocoris pilosulus: rediscovery of a forgotten big-eyed bug taxon from New Caledonia (Heteroptera: Lygaeoidea: Geocoridae) - Kóbor, Péter (Zootaxa, 2020)
Apennocoris pilosulus Montandon, 1907 (Hemiptera: Heteroptera: Lygaeoidea: Geocoridae), a peculiar representative of Geocorinae endemic to New Caledonia unreported since its original description is redescribed and illustrated based on its lectotype (designated in the present paper) and an additional non-type specimen. The placement of this monotypic genus within the subfamily Geocorinae is discussed.